EFFECT OF STARCH AND SULFURIC ACID ON DETERMINATION OF VITAMIN C IN PAPAYA FRUIT USING IODIMETRI - Khoirul Ngibad; M Sungging Pradana; Ingrid Retno Y (Universitas Nahdlatul Ulama Surabaya, 2019)
Vitamin C is an antioxidant that can be used to inactivate oxidation reactions and prevent the formation of free radicals. Sources of vitamin C are fruits, such as papaya fruit. The purpose of this study was to determine the effect of the indicator volume of 1% starch and 2 N sulfuric acid on the determination of vitamin C in papaya fruit samples. This study used the iodimetri method with a standard iodine solution, starch indicator and the addition of sulfuric acid. The variations of starch indicator volume include: 0.25; 0.5, 1, 2 and 3 mL and the variations of sulfuric acid volume include: 0, 2, 4, 6, and 8 mL. The results showed that the optimum 1% starch indicator volume was 1 mL and the optimum volume of 2 N sulfuric acid was 2 mL.